A CORRELATIONAL STUDY OF WORK STRESS AND JOB PERFORMANCE AMONG BANK EMPLOYEES IN ILORIN METROPOLIS - Lasisi, Adekola Kamil; Annor, Patricia Omioguele (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study examined the relationship between work stress and job performance in the banking sector, within Ilorin Metropolis, Kwara State. The research method used was a descriptive survey of correlation type. The target population for this study consisted of all bank employees in Ilorin metropolis, Kwara State. A sample of 120 bank employees was randomly selected for the study. Data collection was done using a questionnaire called the